Environmental Governance in Practice: Strategies of the Environmental Agency in Managing Coastal Coal Waste in Gampong Peunaga Pasi, West Aceh, Indonesia - Jeumpa Aulia; Chairul Iqbal Aziz (Universitas Teuku Umar, 2026)
Coal waste pollution along the coast of Gampong Peunaga Pasi, West Aceh, has become a persistent environmental and socio-economic crisis, disproportionately affecting coastal communities and revealing gaps in local environmental governance. This study analyzes the strategic responses of the West Aceh Environmental Agency (DLH) to the issue, using a qualitative case study approach based on secondary data sources, including policy documents, government reports, media coverage, and environmental regulations. Findings indicate that while DLH has implemented routine strategies such as water quality testing, corporate monitoring, and administrative reporting, these efforts lack enforcement power and fail to generate substantive environmental protection. The agency's actions remain procedural, constrained by limited authority and poor coordination with the provincial environmental office (DLHK Aceh). Additionally, no formal collaboration mechanisms exist between DLH, PT Mifa Bersaudara (the alleged polluter), and affected communities, resulting in governance fragmentation and deepened public distrust. The study also reveals that strong national environmental laws are not matched by institutional empowerment at the local level. Without the authority to sanction violations or compel remediation, DLH’s role becomes largely symbolic. This regulatory disempowerment contributes to recurring ecological harm, economic displacement, and institutional inaction. This case illustrates how decentralized environmental governance in Indonesia struggles with implementation failure and accountability gaps. The study recommends strengthening local enforcement authority, institutionalizing stakeholder collaboration, and ensuring greater transparency and responsiveness in environmental governance to protect vulnerable communities and ecosystems.